Facilitators’ views on content goals, learning obstacles, and teaching resources in reference to conditional probability - Griese, Birgit; Nieszporek, Ralf; Biehler, Rolf

Mathematik-Vorkurse zur Vorbereitung auf das Studium – Zielsetzungen und didaktische Konzepte - Lankeit, Elisa; Biehler, Rolf (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

The role of learning strategies for performance in mathematics courses for engineers - Liebendörfer, Michael; Göller, Robin; Gildehaus, Lara; Kortemeyer, Jörg; Biehler, Rolf; Hochmuth, Reinhard; Ostsieker, Laura; Rode, Jana; Schaper, Niclas (International Journal of Mathematical Education in Science and Technology)
Keywords: Applied Mathematics; Education; Mathematics (miscellaneous)

Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse

Data Science, Statistics, and Civic Statistics: Education for a Fast Changing World - Ridgway, Jim; Campos, Pedro; Biehler, Rolf (Statistics for Empowerment and Social Engagement)

Mini-Aufgaben in mathematischen Übungsgruppen zur Analysis: Charakteristika von Aufgaben und Abstimmungsverhalten von Studierenden - Bauer, Thomas; Biehler, Rolf; Lankeit, Elisa (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

Vorkurse und ihre Wirkungen im Übergang Schule – Hochschule - Lankeit, Elisa; Biehler, Rolf (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

Enriching videos with interactive questions to enhance students’ cognitive activity: concept and implementation - Liebendörfer, Michael; Profeta, Angelo; Krämer, Sandra; Schlüter, Sarah; Becher, Silvia; Biehler, Rolf; Mai, Tobias; Schmitz, Angela

Dokumentation der Erhebungsinstrumente des Projekts WiGeMath - Schürmann, Mirko; Büdenbender-Kuklinski, C.; Lankeit, Elisa; Liebendörfer, Michael; Hochmuth, R.; Biehler, Rolf; Schaper, N.

Einführung in das WiGeMath-Projekt: Wirkung und Gelingensbedingungen von Unterstützungsmaßnahmen für mathematikbezogenes Lernen in der Studieneingangsphase - Hochmuth, Reinhard; Biehler, Rolf; Schaper, Niclas; Liebendörfer, Michael; Büdenbender-Kuklinski, Christiane; Lankeit, Elisa; Ruge, Johanna; Schürmann, Mirko (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

Ein Rahmenmodell für hochschuldidaktische Maßnahmen in der Mathematik - Liebendörfer, Michael; Hochmuth, Reinhard; Biehler, Rolf; Schaper, Niclas; Büdenbender-Kuklinski, Christiane; Lankeit, Elisa; Ruge, Johanna; Schürmann, Mirko (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

Jupyter Notebooks for Teaching, Learning, and Doing Data Science - Fleischer, Yannik; Hüsing, Sven; Biehler, Rolf; Podworny, Susanne; Schulte, Carsten (Bridging the Gap: Empowering and Educating Today’s Learners in Statistics. Proceedings of the Eleventh International Conference on Teaching Statistics)
We report on our work with students in our data science courses, focusing on the analysis of students’ results. This study represents an in-depth analysis of students’ creation and documentation of machine learning models. The students were supported by educationally designed Jupyter Notebooks, which are used as worked examples. Using the worked example, students document their results in a so-called computational essay. We examine which aspects of creating computational essays are difficult for students to find out how worked examples should be designed to support students without being too prescriptive. We analyze the computational essays produced by students and draw consequences for redesigning our worked example.

Profession-Specific Curriculum Design in Mathematics Teacher Education: Connecting Disciplinary Practice to the Learning of Group Theory - Wessel, Lena; Leuders, Timo (Practice-Oriented Research in Tertiary Mathematics Education)

Civic Statistics for Prospective Teachers: Developing Content and Pedagogical Content Knowledge Through Project Work - Podworny, Susanne; Frischemeier, Daniel; Biehler, Rolf (Statistics for Empowerment and Social Engagement)

Data Visualization Packages for Non-inferential Civic Statistics in High School Classrooms - Frischemeier, Daniel; Podworny, Susanne; Biehler, Rolf (Statistics for Empowerment and Social Engagement)

An example of rich, real and multivariate survey data for use in school - Podworny, Susanne; Fleischer, Yannik; Stroop, Dietlinde; Biehler, Rolf

Self-regulated learning in a mathematics course for engineers in the first semester: insights into students reported resource management and cognitive strategies - Kolbe, Tim; Wessel, Lena (Fourth conference of the International Network for Didactic Research in University Mathematics)

Evaluation von Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Schürmann, Mirko; Liebendörfer, Michael; Büdenbender-Kuklinski, Christiane; Lankeit, Elisa; Ruge, Johanna; Schaper, Niclas; Biehler, Rolf; Hochmuth, Reinhard (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

Effects of drawing instructions and strategic knowledge on mathematical modeling performance: Mediated by the use of the drawing strategy - Schönherr, Johanna; Schukajlow, S.; Blomberg, J.; Leopold, C. (Applied Cognitive Psychology, ac3930)

Drawing instructions, strategic knowledge, strategy-based motivation, and students' use of drawings - Schönherr, Johanna; Schukajlow, S.; Leopold, C. (Proceedings of the 45th PME Conference)